Connecting Linkin Park and Good Charlotte to ESL learners - Malachi Edwin Vethamani,; Too, Wei Keong (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2008)
This paper documents students’ response to popular songs in the language classroom and asserts that songs can be a form of useful resource in the language classroom for purposes of language development and to connect learners to issues that are of interest to young adults. This paper reports the findings of a study which used two popular songs in a language classroom to develop reading, writing and speaking skills. The researchers use songs to connect their learners to both the issues in the texts and language elements. The study indicates that students were able to express their viewpoints in relation to the issues in the songs and that the songs, which were familiar to the learners, encouraged them to participate in the classroom activities